Ignition of Al- and B-based dispersed fuels by a radiant heat flux - Korotkikh, Alexander G. (Optics and spectroscopy)
Ignition of Al conglomerate particles and Al-, B-, and AlBn-based dispersed fuels under radiant heating by a cw CO2 laser with heat flux densities q = 65-190 W/cm(2) is experimentally studied. Based on the results obtained, the dependences of the ignition delay time on the heat flux density are determined and a mechanism of ignition of an individual Al particle and dispersed metal fuels in air is described. It is found that the ignition delay times of aluminum bromide micropowders are shorter than those of Al powder by 1.9-2.3 (AlB2) and 3.2-3.5 (AlB12) times under the same heating conditions. The ignition delay times of amorphous boron are minimal (3-10 times shorter than that of Al). The ignition temperatures of AlB2 and AlB12 powders are 110-130 & DEG;C higher than the ignition temperature of aluminum micropowder. With increasing mass concentration of boron in AlB12 particles, the heat release rate upon powder heating and oxidation increases.